Assessing the influence of secure online safe exam browser (SEB) implementation on english language semester examinations - Fadly, Yossy; Purwanto, Dedi; Putri, Ranti Eka; Pratiwi, Nahda Aulia Ade (Institute of Computer Science (IOCS), 2024)
This research examines the effects of implementing the Secure Online Safe Exam Browser (SEB) in English semester exams for undergraduate students in the Accounting program at Universitas Pembangunan Panca Budi (UNPAB). The study seeks to evaluate how SEB impacts students' perceptions regarding ease of use, performance, expectations, and social influence within the context of English language learning. A purposive sampling method was applied, focusing on active students from the 2021, 2022, and 2023 cohorts who used SEB in their English courses. Data were gathered via a structured questionnaire containing Likert-scale items to measure various independent variables alongside the dependent variable of semester exam performance. The results aim to shed light on SEB's effectiveness as a tool for enhancing English language assessment, thereby supporting improved academic outcomes in the Accounting program. This study underscores the importance of integrating technology into educational assessments and its potential to enrich students' learning experiences.